Effects of Resistance Band Training on Arm Muscle Strength and Lob Stroke Performance in Badminton Athletes - Jerry Ananda Putra; Ahmad Chaeroni; Fahmil Haris; Septri (Jurnal Master Penjas & Olahraga, 2026)
This study examined the effect of resistance band training on arm muscle strength and lob stroke performance among PB Apor Payakumbuh badminton athletes. The study used a quasi-experimental one-group pretest-posttest design. The population consisted of 15 athletes, while eight male athletes aged 12-15 years were selected through purposive sampling. Arm muscle strength was measured with a push-up test, and lob performance was measured with a lob accuracy test. The treatment was carried out in 16 resistance band training sessions. Data were analyzed using normality tests and paired-sample t-tests. The results showed significant improvement in push-up performance (p = 0.006) and lob stroke performance (p = 0.000). It can be concluded that resistance band training significantly improves arm muscle strength and lob stroke performance in young badminton athletes.